PERANAN PEMBELAJARAN TEMATIK DALAM TERPADU BAGI PARA ANAK DIDIK SMP DENGAN MEMAKAI KARYA SASTRA SEBAGAI MEDIANYA - Widyahening, CH Evy Tri (UNIVERSITAS SLAMET RIYADI, 2012)
Abstract:Through a thematic study by using an integrated study, it is expected that it can give good benefits for teachers, students, or schools, and also some efforts to increase the quality of teaching learning process. Collaboration in integrated study can make local learning more contextual. Because in integrated study one of subject matter can support the other subject matter. Thereby it is expected that the teaching learning process will be more meaningful.Key words: thematic study, integrated study, the quality of teaching learning process,collaboration.